The Impact of Unemployment on Student Enrollment in Postgraduate Programs in Jordanian Universities - Dr. Mostafa Ali Khlifat; Dr. Sahar Hussien Al Khateeb (Migration Letters, 2023)
The study aimed to find out the effect of unemployment on student enrollment in postgraduate programs in Jordanian universities. To achieve the objectives of the study, a sample of (132) postgraduate (Master’s) students at Al-Balqa Applied University was tested. To analyze the data, arithmetic means, standard deviations, (t) test for independent groups, and one-way analysis of variance were used. Among the most important findings of the study was the presence of an effect of unemployment on the enrollment of students in postgraduate programs in Jordanian universities; also, it showed the presence of an effect of unemployment on the enrollment of students in postgraduate programs in Jordanian universities according to the variable of gender on the dimension of unemployment motive in favor of males, and the presence of an effect of unemployment on student enrollment in postgraduate programs in Jordanian universities according to the variable of age in favor of the age group (25-under 35 years). However, there was no effect of unemployment based on the variable of type of college. The study recommended regulating admission to postgraduate programs, aligning education outputs with the requirements of the labor market, educating young people about the required specializations, finding solutions that limit the problem of unemployment, and conducting more studies and research on this problem.